Expression of p63 as predictive and prognostic factor in advanced non-small-cell lung cancer - Cvetkovič, Gordana Ž; Plavec, Goran; Tatomirović, Željka; Jović, Milena; Lončarević, Olivera; Trifunović, Zoran; Vuković, Jelena; Stojsavljević, Marko; Milić, Gordana (Vojnosanitetski pregled, 2020)
AbstractBackground/Aim. Serbia belongs to the group of countries with a high lung cancer incidence and mortality rate. p63 gene plays an important role in development of lung cancer and immunohistochemical expression of p63 is considered to be a reliable marker for squamous histology. The results of some in vitro studies show a significant association of p63 expression and cisplatin chemoresistance. The aim of this study was to estimate the significance of p63 expression as predictive and prognostic factor in advanced non-small-cell lung cancer (NSCLC). Methods. Expression of p63 in 85 NSCLC (stages III, and IV) was investigated by the use of immunohistochemistry. Four weeks after the completion of 2 cycles of platinum-based doublet chemotherapy all the patients were evaluated based on the treatment response. Kaplan-Meier analysis with log-rank tests were used for overall survival (OS) and progression free survival (PFS) calcultations. Results. The expression of p63 was present in 49.4% of the patients out of whom 38.8% were with positive expression (p63+) and 10.6% of the patients were with weak expression (p63+-). Positive expression of p63 was seen in 93.9% of squamous cell carcinomas (SQCC), 5% of adenocarcinomas (AC), and in no patient with not otherwise specified (NOS) NSCLC. Weak expression of p63 was found in 12.5% of AC, 25% of NOS and only in 3% of SQCC. Analysis of the impact of the presence of p63 expression on the initial response to chemotherapy showed no statistical significance. The patients with weak p63 expression had a significantly shorter OS than the patients with no p63 expression (p = 0.049), and the tendency of shorter OS than the patients with p63 expression (p = 0.068). Conclusion. This study shows that p63 expression has no predictive significance for tumor response to initial chemotherapy regimen gemcitabine/cisplatin or paclitaxel/cisplatin observed in advanced NSCLC. Weak expression of p63 have a negative prognostic effect in stage III and IV NSCLC.
Keywords: carcinoma, non-small-cell lung; neoplasm staging; immunohistochemistry; disease progression; predictive value of tests.